A method for preparing a ceramic material for semiconductor
By adding modified polyethyleneimine and nanotitanium dioxide to the alumina ceramics, the problem of insufficient strength and conductivity of alumina ceramics is solved, and the high density and high conductivity of ceramic materials are achieved, which is suitable for high-performance semiconductor devices.
Patent Information
- Application Number
- CN202411450404.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing alumina ceramics for semiconductors have low strength and poor conductivity, making it difficult to meet the needs of high-performance semiconductor devices.
By adding modified polyethyleneimine and nanotitanium dioxide to the alumina ceramic material, the alumina is modified by using the reactive amine functional groups of the modified polyethyleneimine, and its dispersion is improved through the coordination effect of the nanotitanium dioxide to form a ceramic material with high density and high conductivity.
It significantly improves the bending strength and conductivity of ceramic materials, reduces the resistivity, and makes alumina ceramics more widely used in semiconductor devices and other fields.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor ceramics, in particular to a method for preparing a semiconductor ceramic material. Background Art
[0002] Alumina ceramics have excellent mechanical, thermal and wear-resistant properties and are widely used in advanced ceramic materials, semiconductor ceramic substrates, aerospace and other fields. Doping alumina ceramics with semiconductor materials such as rare earth oxides, titanium dioxide, and hafnium dioxide can improve the conductivity of alumina ceramics and expand their practical applications in semiconductor devices.
[0003] Nano-titanium dioxide has the characteristics of small particle size, large specific surface area, high strength, and unique semiconductor properties. Adding nano-titanium dioxide to alumina ceramic materials can improve the comprehensive performance of ceramic materials. The invention patent with announcement number CN114560685B discloses alumina ceramics and their preparation methods and applications. Alumina, titanium dioxide, magnesium oxide, calcium oxide, silicon oxide, iron oxide, cobalt oxide, chromium oxide, etc. are used as raw materials. The obtained alumina ceramics have more suitable mechanical properties, dielectric constants, thermal expansion coefficients and thermal conductivity, and can be used in the packaging field of semiconductor devices and image sensors. However, the raw materials of the alumina ceramics are relatively complicated, and do not show good bending strength and electrical conductivity. Summary of the invention
[0004] The invention solves the problem that the alumina ceramics used for semiconductors have low strength and poor electrical conductivity.
[0005] The technical solution provided by the present invention is: a method for preparing a ceramic body for semiconductor use:
[0006] (1) Add polyethyleneimine, 3,4-dihydroxybenzaldehyde (CAS registration number 139-85-5), and glacial acetic acid to the solvent, stir for reaction, and then distill under reduced pressure. Add water and sodium hydroxide to neutralize. Place the product in a dialysis bag and dialysis purification to obtain catechol-modified polyethyleneimine. The reaction formula is:
[0007] .
[0008] (2) Add water, catechol-modified polyethyleneimine, and alumina into a planetary ball mill, perform a ball milling, then add nano-titanium dioxide, perform a ball milling, then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor use.
[0009] Preferably, in (1), the solvent is ethanol or methanol.
[0010] Preferably, in (1), the mass of 3,4-dihydroxybenzaldehyde and glacial acetic acid are 5%-30% and 0.8%-5% of the mass of polyethyleneimine, respectively.
[0011] Preferably, in (1), the mass fraction of glacial acetic acid is ≥ 95%.
[0012] Preferably, in (1), the reaction temperature is 30-45°C and the reaction time is 6-12h.
[0013] Preferably, in (2), the mass of catechol-modified polyethyleneimine and nano-titanium dioxide are 2%-10% and 0.2%-3% of the mass of aluminum oxide, respectively.
[0014] Preferably, in (2), the ratio of alumina to water is (350-450) g:1L.
[0015] Preferably, in (2), the time of the first ball milling is 4-6 hours, and the time of the second ball milling is 2-3 hours; the rotation speed during ball milling is 400-600 r / min.
[0016] Technical effect: The present invention adds modified polyethyleneimine and nano-titanium dioxide when preparing the alumina ceramic body. The modified polyethyleneimine molecular chain contains rich active amine functional groups and has a strong interaction with the alumina surface, which can modify the alumina well, thereby reducing the agglomeration of alumina and improving its dispersibility. After high-temperature sintering, the density and relative density of the semiconductor ceramic material are significantly improved, and the flexural strength is also significantly increased.
[0017] The modified polyethyleneimine of the present invention can not only modify alumina, but also contains a catechol structure. During the ball milling process, the catechol structure can coordinate with the surface of nano-titanium dioxide, so that the nano-titanium dioxide is uniformly attached to the surface of the alumina, thereby improving the dispersibility of the nano-titanium dioxide. The nano-titanium dioxide has the characteristics of large surface area and unique nano-small size effect, and can be filled in the gaps of the alumina ceramic body to increase the bonding area between the alumina particles and support the matrix skeleton. After high-temperature sintering, the compactness and relative density of the semiconductor ceramic material are significantly improved, and the bending strength is also significantly increased.
[0018] When the ceramic body of the present invention is sintered in an atmosphere of nitrogen and hydrogen, the nano-titanium dioxide crystals form oxygen vacancies, and the free electrons in the oxygen vacancies interact with the Ti of the titanium dioxide. 4+ Ion combination makes Ti 4+ Ion reduction generates Ti 3+ ions, in Ti 3+At high temperatures, the ions react with the alumina grains to form a solid solution, so that the freely moving electrons are distributed in the alumina ceramic matrix, which significantly improves the conductivity of semiconductor ceramic materials and reduces the resistivity, making the alumina coating have better practical applications in aspects such as semiconductor device ceramic substrates. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with the examples. The raw materials of the examples and comparative examples of the present invention are all commercially available unless otherwise specified.
[0020] The average particle size of the aluminum oxide of the present invention is 5 μm, and the average particle size of the nano titanium dioxide is 20 nm.
[0021] Example 1
[0022] (1) Add 5 g of polyethyleneimine, 0.87 g of 3,4-dihydroxybenzaldehyde, and 0.16 g of 95% glacial acetic acid to 80 mL of ethanol solvent, stir and react at 40 °C for 12 h, distill under reduced pressure, add water, and neutralize with sodium hydroxide. Place the product in a dialysis bag and purify it by dialyzing to obtain catechol-modified polyethyleneimine.
[0023] (2) Add 1L of water, 8g of catechol-modified polyethyleneimine, and 400g of alumina to a planetary ball mill, control the ball mill speed to 600r / min, and ball mill for 4h. Then add 0.8g of nano-titanium dioxide and ball mill for 2h. Then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor.
[0024] Example 2
[0025] (1) Add 5 g of polyethyleneimine, 0.55 g of 3,4-dihydroxybenzaldehyde, and 0.09 g of 95% glacial acetic acid to 100 mL of methanol solvent, stir and react at 30 °C for 12 h, distill under reduced pressure, add water, and neutralize with sodium hydroxide. Place the product in a dialysis bag and purify it by dialyzing to obtain catechol-modified polyethyleneimine.
[0026] (2) Add 1L of water, 18g of catechol-modified polyethyleneimine, and 450g of alumina to a planetary ball mill, control the ball mill speed to 400r / min, and ball mill for 6h. Then add 3.6g of nano-titanium dioxide and ball mill for 2h. Then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor.
[0027] Example 3
[0028] (1) Add 5 g of polyethyleneimine, 0.25 g of 3,4-dihydroxybenzaldehyde, and 0.04 g of 98% glacial acetic acid to 80 mL of methanol solvent, stir and react at 30 °C for 6 h, distill under reduced pressure, add water, and neutralize with sodium hydroxide. Place the product in a dialysis bag and purify it by dialyzing to obtain catechol-modified polyethyleneimine.
[0029] (2) Add 1L of water, 24g of catechol-modified polyethyleneimine, and 400g of alumina to a planetary ball mill, control the ball mill speed to 400r / min, and ball mill for 6h. Then add 6g of nano-titanium dioxide and ball mill for 2h. Then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor.
[0030] Example 4
[0031] (1) Add 5 g of polyethyleneimine, 1.5 g of 3,4-dihydroxybenzaldehyde, and 0.25 g of 95% glacial acetic acid to 110 mL of ethanol solvent, stir and react at 35 °C for 12 h, distill under reduced pressure, add water, and neutralize with sodium hydroxide. Place the product in a dialysis bag and purify it by dialyzing to obtain catechol-modified polyethyleneimine.
[0032] (2) Add 1L of water, 28g of catechol-modified polyethyleneimine, and 350g of alumina to a planetary ball mill, control the ball mill speed to 500r / min, and ball mill for 4h. Then add 7.7g of nano-titanium dioxide and ball mill for 3h. Then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor.
[0033] Example 5
[0034] (1) Add 5 g of polyethyleneimine, 1.22 g of 3,4-dihydroxybenzaldehyde, and 0.2 g of 98% glacial acetic acid to 90 mL of ethanol solvent, stir and react at 45 °C for 6 h, distill under reduced pressure, add water, and neutralize with sodium hydroxide. Place the product in a dialysis bag and purify it by dialyzing to obtain catechol-modified polyethyleneimine.
[0035] (2) Add 1L of water, 40g of catechol-modified polyethyleneimine, and 400g of alumina to a planetary ball mill, control the ball mill speed to 600r / min, and ball mill for 5h. Then add 12g of nano-titanium dioxide and ball mill for 3h. Then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor.
[0036] Comparative Example 1
[0037] (1) Add 1L of water and 400g of alumina to a planetary ball mill, control the ball mill speed to 600r / min, and ball mill for 4h. Then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor use.
[0038] Comparative Example 2
[0039] (1) Add 1L of water, 8g of catechol-modified polyethyleneimine, and 400g of alumina to a planetary ball mill, control the ball mill speed to 600r / min, and ball mill for 4h. Then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor use.
[0040] Comparative Example 3
[0041] (1) Add 1L of water and 400g of alumina to a planetary ball mill, control the ball mill speed to 600r / min, ball mill for 4h, then add 0.8g of nano-titanium dioxide, ball mill for 2h, then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor.
[0042] Comparative Example 4
[0043] (1) Add 1L of water, 8g of polyethyleneimine, and 400g of alumina to a planetary ball mill, control the ball mill speed to 600r / min, and ball mill for 4h. Then add 0.8g of nano-titanium dioxide and ball mill for 2h. Then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor.
[0044] Comparative Example 5
[0045] (1) Add 5 g of polyethyleneimine, 0.87 g of 4-hydroxybenzaldehyde, and 0.16 g of 95% glacial acetic acid to 80 mL of ethanol solvent, stir and react at 40 °C for 12 h, distill under reduced pressure, add water, and neutralize with sodium hydroxide. Place the product in a dialysis bag and purify it by dialyzing to obtain modified polyethyleneimine.
[0046] (2) Add 1L of water, 8g of modified polyethyleneimine, and 400g of alumina to a planetary ball mill, control the ball mill speed to 600r / min, and ball mill for 4h. Then add 0.8g of nano-titanium dioxide and ball mill for 2h. Then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a ceramic green body for semiconductor.
[0047] The semiconductor ceramic body prepared in each embodiment and comparative example was placed in a vacuum sintering furnace, sintered at 1500°C for 1 hour at 10 MPa, and then a mixed gas of nitrogen and hydrogen with a volume ratio of 95:5 was introduced, sintered at 1500°C for 3 hours, and cooled to obtain a semiconductor ceramic material.
[0048] The relative density of semiconductor ceramic materials was tested according to the Archimedes method. Each sample was tested 5 times and the average value was taken.
[0049] The three-point bending method was used to test the flexural strength of semiconductor ceramic materials. The sample size was 35 mm × 4 mm × 3 mm and the loading rate was 0.5 mm / min.
[0050] The resistivity of semiconductor ceramic materials was tested by the three-ring electrode method using an insulating material high temperature resistivity tester. The test results are shown in Table 1.
[0051] Table 1 Performance test of ceramic materials for semiconductors
[0052]
[0053] After testing, compared with Comparative Example 1, Comparative Example 2 added catechol-modified polyethyleneimine, whose polyethyleneimine molecular chain contains abundant active amine functional groups, has strong interaction with the surface of alumina, can modify alumina well, is conducive to reducing the agglomeration of alumina, improves its dispersibility, and significantly improves the compactness and relative density of the ceramic material after high-temperature sintering, and significantly increases the bending strength. However, the resistivity is large and the conductivity is poor.
[0054] Compared with comparative example 1, comparative example 3 adds nano titanium dioxide, which has the characteristics of high strength, small particle size, large surface area and unique nano small size effect. Nano titanium dioxide can be filled in the gaps of the alumina ceramic body, increasing the bonding area between alumina particles and supporting the matrix skeleton. After high-temperature sintering, the compactness and relative density of the ceramic material are significantly improved, and the bending strength is also significantly increased. When sintered in a nitrogen and hydrogen atmosphere, the crystals of nano titanium dioxide form oxygen vacancies, and the free electrons in the oxygen vacancies react with the Ti of titanium dioxide. 4+ Ion combination makes Ti 4+ Ion reduction generates Ti 3+ ions, in Ti 3+ At high temperature, the ions undergo solid solution reaction with the alumina grains, so that the freely moving electrons are distributed in the alumina ceramic matrix, which significantly improves the conductivity of the ceramic material and reduces the resistivity.
[0055] The semiconductor ceramic blanks in Examples 1-5 are added with modified polyethyleneimine and nano-titanium dioxide. The modified polyethyleneimine can not only modify alumina, which is beneficial to reduce the agglomeration of alumina and improve its dispersibility, but also contains a catechol structure. During the ball milling process, the catechol structure can coordinate with the surface of nano-titanium dioxide, so that the nano-titanium dioxide is uniformly attached to the surface of alumina, and the dispersibility of the nano-titanium dioxide in the ceramic blank is improved, so that the nano-titanium dioxide is more uniformly filled in the gaps of the ceramic blank. After high-temperature sintering, the relative density and flexural strength of the ceramic material are significantly improved. In addition, the resistivity is significantly reduced, and the conductive performance is better.
[0056] The polyethyleneimine and modified polyethyleneimine added to the ceramic bodies of Comparative Examples 4 and 5 do not contain a catechol structure and cannot coordinate with the surface of nano-titanium dioxide, resulting in difficulty in uniformly adhering nano-titanium dioxide to the surface of alumina and poor dispersion. After high-temperature sintering, the relative density and flexural strength of the ceramic material are lower than those of the embodiments, and the resistivity is higher than that of the embodiments, and the conductive performance is poor.
[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.
Claims
1. A method for preparing a semiconductor ceramic material, characterized in that: The preparation method is: (1) Add polyethyleneimine, 3,4-dihydroxybenzaldehyde and glacial acetic acid to a solvent, stir for reaction and then distill under reduced pressure, add water and sodium hydroxide to neutralize, place the product in a dialysis bag, and dialysis and purification to obtain catechol-modified polyethyleneimine; (2) Add water, catechol-modified polyethyleneimine, and alumina to a planetary ball mill, perform a ball milling, then add nano-titanium dioxide, perform a ball milling, then pour the slurry into a mold, dry it, and finally press the material into a green body to obtain a semiconductor ceramic green body; (3) placing the semiconductor ceramic body in a vacuum sintering furnace, sintering at 1500° C. for 1 h at 10 MPa, then introducing a mixed gas of nitrogen and hydrogen with a volume ratio of 95:5, sintering at 1500° C. for 3 h, and cooling to obtain a semiconductor ceramic material; Said (1), the mass of 3,4-dihydroxybenzaldehyde and glacial acetic acid is 5%-30% and 0.8%-5% of the mass of polyethyleneimine respectively; Said (1), the reaction temperature is 30-45 ℃, time is 6-12h; In the above (2), the mass of catechol-modified polyethyleneimine and nano-titanium dioxide are 2%-10% and 0.2%-3% of the mass of aluminum oxide, respectively.
2. The method for preparing a semiconductor ceramic material according to claim 1, characterized in that: In the above (1), the solvent is ethanol or methanol.
3. The method for preparing a semiconductor ceramic material according to claim 1, characterized in that: In the above (1), the mass fraction of glacial acetic acid is ≥ 95%.
4. The method for preparing a semiconductor ceramic material according to claim 1, characterized in that: In the above (2), the ratio of alumina to water is (350-450) g:1L.
5. The method for preparing a semiconductor ceramic material according to claim 1, characterized in that: In the above (2), the time of the first ball milling is 4-6 hours, and the time of the second ball milling is 2-3 hours; the rotation speed during ball milling is 400-600 r / min.
Citation Information
Patent Citations
Alumina ceramics, their preparation methods and applications
CN114560685B
Preparation method of TiO2-polyethyleneimine-graphene composite adsorbing and degrading material
CN112495354A
Catechol modified polyethyleneimine water-based adhesive and synthesis method thereof
CN115991973A